Risk of desmoid formation after laparoscopic versus open colectomy and ileorectal anastomosis for familial adenomatous polyposis. Issue 6 (8th August 2018) - Sinha, A.; Burns, E. M.; Latchford, A.; Clark, S. K.
Abstract : Background: Laparoscopy is used increasingly in prophylactic surgery for patients with familial adenomatous polyposis (FAP) undergoing colectomy with ileorectal anastomosis (IRA). Little is known about the impact of laparoscopy on subsequent desmoid risk. This study documented the risk of desmoid in patients undergoing laparoscopic and open IRA. Methods: This was an observational study of patients with FAP and known germline APC mutation, undergoing IRA at a tertiary referral centre between 1996 and 2016. Patients were retrieved from a prospectively maintained polyposis registry. Data included genotype, family history of desmoid, sex, surgical approach at IRA and postoperative complications. The main outcome was development of either a clinically or radiologically significant desmoid. Results: Some 112 patients (61 female) underwent colectomy and IRA. A laparoscopic approach was used in 69 patients (61·6 per cent). Baseline characteristics did not differ between patients having an open or laparoscopic approach. Median follow‐up was 5·8 (i.q.r. 2·4–11·2) years. Patients who underwent laparoscopic IRA had a reduced risk of desmoid formation (3 of 69 (4 per cent) versus 7 of 43 (16 per cent) in the open group; P  = 0·043). Discussion: Laparoscopic IRA may reduce risk of subsequent desmoid formation in patients with FAP. Abstract : Laparoscopic ileorectal anastomosis is safe for appropriately selected patients with familial adenomatous polyposis and can reduce risk of subsequent desmoid formation. Laparoscopy associated with less desmoid tumours